2015
DOI: 10.1007/978-3-319-22668-2_14
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Effects of Three Think-Aloud Protocols on Identification of Usability Problems

Abstract: Think-aloud is a de-facto standard in user-based usability evaluation to verbalize what a user is experiencing. Despite its qualities, it has been argued that thinking aloud affects the task solving process. This paper reports from an empirical study of the effect of three think-aloud protocols on the identified usability problems. The three protocols were traditional, active listening and coaching. The study involved 43 test subjects distributed on the three thinkaloud conditions and a silent control conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Across the analysis, the evaluators had an any-two agreement of 0.44 (SD = 0.11), which is relatively high compared to other studies [3]. Further information about the data collection can be found in [1].…”
Section: Data Collectionmentioning
confidence: 79%
“…Across the analysis, the evaluators had an any-two agreement of 0.44 (SD = 0.11), which is relatively high compared to other studies [3]. Further information about the data collection can be found in [1].…”
Section: Data Collectionmentioning
confidence: 79%
“…The interactive and relaxed think-aloud protocol applied in the study is the most used protocol in usability testing [21]. The chosen think-aloud protocol affects very little on the number and type of usability problems found [24]. Therefore, we must emphasize that, in this setting, the test participants brought up the privacy issues naturally and spontaneously in discussion about system features and usability.…”
Section: Discussionmentioning
confidence: 99%
“…Olmsted-Hawala et al [25] found that relaxed thinking aloud yielded higher satisfaction with the website than classic thinking aloud and higher task completion rates than both classic thinking aloud and the control condition. Bruun and Stage [4] found that classic and relaxed thinking aloud revealed more usability problems than the control condition; there was no difference between the two thinking-aloud conditions. These authors note that thinking aloud "led to data from which we could enrich problem descriptions to include notions of why a particular problem was observed.…”
Section: Recommendations For Moderator Verbalizationsmentioning
confidence: 93%